Expression of heat shock proteins (Hsps) 27 and 70 in kidney in cases of fatal hemorrhage. (July 2022) - Doberentz, E.; Wegner, A.; Rochlitzer, L.; Madea, B.; Ulbricht, J.
Abstract: The expression levels of intracellular heat shock proteins (Hsps), specialized chaperone proteins, increase in cases of cellular stress with protein misfolding and aggregation. In a previous study, we demonstrated that there is an extensive increase in intracellular Hsp27 and 70 expression levels in renal tissues in fire fatality cases. Hsp expression can be induced by not only heat, but also by tissue hypoxia. In cases of fatal hemorrhage, the individual suffers hypoxemia and consequently tissue hypoxia. Here, we examined 43 cases of fatal hemorrhage and a control group of 85 deaths not related to blood loss or temperature exposure. We evaluated Hsp27 and 70 protein expression levels in renal tissue using immunohistochemistry. The results revealed that no extensive Hsp27 or 70 expression is induced in the fatal hemorrhage cases. The renal Hsp levels were similar to those of the control group. Fatal blood loss does not cause relevant cell stress. Highlights: Tissue hypoxia can cause cellular stress even leading to cell death. Hsps are expressed in case of cell stress to maintain protein homeostasis. Persistent hypoxidosis causes micromorphological alterations. Renal tissue is very sensitive to hypoxia. Fatal hemorrhage does not cause an extensive hsp expression.